Maternal prenatal psychological distress associates with offspring early‐life wheezing – FinnBrain Birth Cohort. Issue 1 (5th December 2021) - Puosi, Emma; Korhonen, Laura S.; Karlsson, Linnea; Kataja, Eeva‐Leena; Lukkarinen, Heikki; Karlsson, Hasse; Lukkarinen, Minna
Abstract: Background: Exposure to prenatal maternal psychological distress may contribute to the development of childhood atopic disorders. Little is known about the importance of distress severity and its duration for the risk. Our aim was to investigate how chronic maternal depressive and anxiety symptoms across gestation influence the risk of wheezing and eczema at child age 24 months. Methods: The study population was drawn from the FinnBrain Birth Cohort Study, including 1305 mother‐infant dyads followed across gestation until the child age of 24 months when the outcomes were mother‐reported wheezing ever and doctor‐diagnosed eczema. To investigate the risk of wheezing phenotypes, wheezing with and without eczema was separated. Maternal distress was assessed with the Edinburgh Postnatal Depression Scale for depressive and the Symptom Checklist‐90 for anxiety symptoms three times during pregnancy, and the chronicity was demonstrated using symptom trajectories composed by latent growth mixture modeling. Results: Of the children, 219/1305 (17%) had wheezing ever and 285/1276 (22%) had eczema. Risk of wheezing ever was elevated with maternal consistently high depressive symptoms (adjusted odds ratio 2.74; 95% confidence interval 1.37–5.50) or moderate and increasing anxiety symptoms (1.94; 1.06–3.54, respectively). Similarly, wheezing without eczema was associated with consistently high depressive (3.60; 1.63–7.94, respectively) and moderate and increasing anxiety symptoms (2.43; 1.21–4.91, respectively). Conclusions: Maternal chronic psychological distress across gestation was associated with toddler wheezing and especially wheezing without other atopic features (eczema). This finding supports the theory of intrauterine programming effect by maternal psychological distress on offspring immune system and respiratory morbidity.